LONG-TERM OUTCOMES IN RHEUMATOID ARTHRITIS IN RELATION TO THE TIME AFTER THE INITIATIONOF BASIC ANTI-INFLAMMATORY DRUG THERAPY - Natalya Vladimirovna Chichasova; M Z Kanevskaya; G R Imametdinova; E V Igolkina; E L Nasonov (Научно-практическая ревматология, 2010)
The paper presents the long-term outcomes of rheumatoid arthritis (RA) according to the data of a 15-year prospective follow-up and treatment in 240 patients with the disease. Disease activity resistance (stable remission of more than 2 years, a recurring course with druginduced remissions of 6-18 months, or no remissions), the degree of joint destruction progression, the functional state of patients and their survival were assessed in relation to the time of use of basic anti-inflammatory drugs (BAIDs). In groups 1, 2, and 3, BAID therapy was initiated within the first 5 months of RA, 6-11 and 12-36 months after its onset, respectively. The treatment was monitored, by estimating clinical and X-ray parameters, the functional state of the locomotor apparatus and by correcting the therapy at its stages in the absence of reliable suppression of RA activity and/or with the continuing emergence of new erosions in small joints. The early use of BAIDs under meticulous control of the degree of RA activity suppression and RA progression were shown to frequently achieve clinical and laboratory remissions and to improve functional and life prognosis in the patients.